Pengaruh fraksi konsentrasi nanokomposit Fe3O4/PANi dengan metode sol-gel spin coating untuk material elektroda baterai lithium (Effect of Fe3O4 / PANi nanocomposite concentration fraction by sol-gel spin coating method for lithium battery electrode material ) - Varadila Sahanaya; - Ramli; Yenni Darvina (Department of Physics – Universitas Negeri Padang UNP, 2018)
In this modern era, technological developments in the field of electronic devices are progressing very rapidly. Therefore, this triggers the demand for storage of electrical energy, one of which is a lithium battery. The performance of the lithium battery depends on the electrode material used. The purpose of this study was to investigate the effect of Fe3O4 concentration on Fe3O4/PANi nanocomposite electrical properties by sol gel method for lithium battery electrode material. In this study, the growth of Fe3O4/PANi nanocomposite layers using spin coating method with a concentration variation of 30%, 40%, 50%, 60% and 70%. Magnetite was prepared using sol-gel technique with precursors (Fe(NO3)3.9H2O). Then the precursor was mixed with PANi polymer with varied concentrations. The results of Fe3O4/PANi Gel are coated on a glass substrate followed by a drying process. Fe3O4/PANi nanocomposite layers were characterized using X-Ray Diffraction and Scanning Electron Microscopy and LCR meters. The results of this study indicate that at a concentration of 30% to a concentration of 40% there is a decrease but at a concentration of 50% an increase in the size of the crystal and at a concentration of 60% to 70% decreased again. FTIR results show the molecular bond formed and the results of SEM imaging show the thickness of the nanocomposite layer. As well as conductivity and electrical capacitance obtained through characterization using LCR meters which are 6.91218303 S/cm and 2.69 x10-10F.